Upaya Promotif Kesehatan Metabolik melalui Identifikasi Prediabetes dan Edukasi Kopi Sehat pada Pegawai BKKBN di Sumatera Utara: Metabolic Health Promotion Efforts through Identification of Prediabetes and Healthy Coffee Education for BKKBN Employees in North Sumatra - Nasution, Huwainan Nisa; Febriyanti, Eka; Lufiana, Fardella (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Prediabetes is a condition characterized by glucose or HbA1C levels that do not meet the criteria for diabetes but have abnormal carbohydrate metabolism that results in abnormal glucose levels between normoglycemia and diabetes. Early screening in young adults is an effort to prevent progression to diabetes mellitus. On the other hand, coffee consumption habits in young adults, including office workers, affect glucose metabolism and insulin sensitivity. This activity aims to identify prediabetes status in employees of Badan Kependudukan dan Keluarga Berencana Nasional (BKKBN) in North Sumatra through fasting blood glucose level examinations, as well as providing education about prediabetes and healthy coffee. The methods used include interactive counseling and fasting blood glucose level examinations using spectrophotometry techniques. The results of the activity showed that 26.7% of participants suffered from prediabetes, and most of them did not know the relationship between coffee consumption and prediabetes. Conclusion: This activity increased participants' knowledge and awareness of healthy coffee and efforts to prevent prediabetes.